Smoking cessation strategies for women: An analysis of smoking cessation determinants among Korean female smokers participating in a smoking cessation outreach program - Minhee Suh; Boae Im; Hun Jae Lee; Kyu-Sung Kim; Min Sohn (Tabriz University of Medical Sciences, 2023)
Background: Although there is strong evidence that behavioral counseling improves quit rates, limited data are available on individualized smoking cessation counseling provided to female smokers because they often are hesitant to identify as smokers. This study aimed to elucidate factors related to smoking cessation among Korean women who participated in the smoking cessation outreach program. Methods: This retrospective descriptive study used data retrieved from the Korea Health Promotion Institute. The data included individual participant characteristics, supportive services received, and self-reported smoking cessation outcomes from June 1, 2015, to December 31, 2017. Results: Data from 709 women were analyzed. We found cessation rates of 43.3% (confidence interval [CI]=0.40, 0.47) at four weeks, 28.6% (CI=0.25, 0.32) at 12 weeks, and 21.6% (CI=0.19, 0.25) at six months. Significant determinants of quitting at six months were regular exercise (odds ratio [OR]=3.02; 95% CI=1.28, 3.29; P=0.009) and the number of counseling sessions during the first four weeks of the program (OR=1.26; 95% CI=1.04, 1.82; P=0.041). Conclusion: Providing intensive counseling during initial phase of smoking cessation program and regular exercise would be effective strategies for smoking cessation programs for women smokers to promote their health.